A Comparative Analysis of Learning Outcomes in The Faculty of Education in Indonesia, Malaysia, and Singapore - Ahmad Royani; Lu’luil Maknun; Iis Susiawati; Kisno Umbar (Jurnal Basicedu, 2022)
The focus of this Research aims to obtain a picture of learning outcomes at the S1 level, especially in the faculty of education in Indonesia, Malaysia and Singapore. Learning outcomes are designed to face the era of the global market (MEA). Learning outcomes are a set of learning outcomes aimed at improving the quality of education in Indonesia. Learning Outcomes consists of education and training. The sub focus of this research is to find out whether learning outcomes are applied according to market needs, or there are still learning outcomes that need to be recommended for the IQF curriculum in Indonesia. This research method is qualitative and quantitative. Data obtained from curriculum documents and laws in force in Indonesia, Malaysia and Singapore. Data collection techniques by observation, interview and documentation. The results of the study showed that there were similarities in learning outcomes in the aspects of curriculum objectives, namely to equip students with life skills. The difference is in terms of character building and independence and responsibility.